МОДЕЛИРОВАНИЕ ПРОЦЕССА ГИПЕРГЕНЕЗА НА ВУЛКАНАХ С ИСПОЛЬЗОВАНИЕМ ВАКУУМА [НА ПРИМЕРЕ ЛЕСЮКИТА Аl2(ОН)5Сl · 2Н2О - Филатов С.К.; Пауфлер П.; Вергасова Л.П.; Левин А.А.; Янсон О.М.; Майер Д.К. (My University, 2005)
The new bauxite mineral - lesukite Al2(OH)5C1 2H2O - was investigated in vacuum (down to 10-7 bar), experiment 1, and forevacuum (down to 10-5 bar), experiment 2, at room temperature. It is shown, that in case of atmosphere conditions lesukite dehydrates and becomes decomposed at +140 °C, but in vacuum conditions (10-6-10-7 bar) its dehydration and amorphisation occur even at room temperature; dehydration is accompanied by decrease of the cubic cell parameter (a = 19.82 Å) by 1 Å (5 %). So vacuum treatment may be used for «pum-ping out» the weak-bonded water from the matter, like heating. Dehydration in vacuum may be proceeded at lo-wer temperatures than in atmosphere conditions. This fact may be of interest in geology and technology.
Keywords: 551.215:511.311:549.01.057:62/982